Ice Loads : 2024 IBC and ASCE/SEI 7-22 - Fanella, David A. (McGraw-Hill's AccessEngineering., 2023)
This Excel workbook determines ice loads in accordance with the 2024 IBC and ASCE/SEI 7-22. Ice load calculations are performed in Imperial and metric units for chimneys and tanks and for solid freestanding walls and signs.